The Enabling Environment for Social Accountability in Mongolia - World Bank (Washington, DC, 2012)
The purpose of this study on the enabling environment for social accountability in Mongolia is: 1) to analyze conditions that influence the ability of citizens and their organizations to promote accountability of public institutions in Mongolia; 2) to identify priority areas for policy, legal, regulatory, and institutional reforms to improve these conditions; and 3) to identify areas in which the capacity building of civil society organizations and the Government of Mongolia may be promoted to enhance social accountability for improved governance, social and economic development, and poverty reduction. The study applies a civic engagement analytical framework to assess the enabling environment: the factors and conditions that would allow Civil Society Organizations (CSOs) to promote public accountability. This framework, represented by the acronym ARVIN, recognizes five enabling elements of civic engagement, namely, the ability of citizens to: Associate to further their purposes; mobilize appropriate Resources; exercise their Voice; gain access to Information that is relevant, timely, and accessible; and Negotiate with government through established mechanisms and rules of engagement. The study concludes that while impressive strides have been made since the transition from socialism, particularly in comparison with other governments in the region, Mongolia continues to face significant institutional, legal, and sociopolitical obstacles to effective social accountability. Since middle- and lower-level public officials are often more resistant to civic engagement, Government of Mongolia and political leaders must lead reform not only of the legal structure and governmental institutions but also of Mongolia's political culture to promote an enabling environment for social accountability.